A synthesis of transplant experiments and ecological niche models suggests that range limits are often niche limits. (25th April 2016) - Lee‐Yaw, Julie A.; Kharouba, Heather M.; Bontrager, Megan; Mahony, Colin; Csergő, Anna Mária; Noreen, Annika M.E.; Li, Qin; Schuster, Richard; Angert, Amy L.
Abstract: Global change has made it important to understand the factors that shape species' distributions. Central to this area of research is the question of whether species' range limits primarily reflect the distribution of suitable habitat (i.e. niche limits) or arise as a result of dispersal limitation. Over‐the‐edge transplant experiments and ecological niche models are commonly used to address this question, yet few studies have taken advantage of a combined approach for inferring the causes of range limits. Here, we synthesise results from existing transplant experiments with new information on the predicted suitability of sites based on niche models. We found that individual performance and habitat suitability independently decline beyond range limits across multiple species. Furthermore, inferences from transplant experiments and niche models were generally concordant within species, with 31 out of 40 cases fully supporting the hypothesis that range limits are niche limits. These results suggest that range limits are often niche limits and that the factors constraining species' ranges operate at scales detectable by both transplant experiments and niche models. In light of these findings, we outline an integrative framework for addressing the causes of range limits in individual species.